The Legislative Function of the House of Representatives to Prevent and Eradicate of Corruption - Jaidun Jaidun (Faculty of Law, Universitas Pekalongan, 2023)
The House of Representatives through its legislative function can renew or replace the existing Law on the eradication of corruption with a new Law on the prevention and eradication of corruption that is effective and radical in preventing and eradicating corruption. The establishment of laws to prevent and eradicate corruption is a mandate of the people that must be realized by the House of Representatives through the legislative function, in order to realize the welfare and intellectual life of the nation, while law enforcement officials are unable to prevent and eradicate corruption completely, due to the principle of legality and the mentality of law enforcement officials. Legally, preventing and eradicating corruption must have a legal basis that is made and stipulated by the House of Representatives together with the President. The establishment of the Law on the prevention and eradication of corruption must be able to ensnare the perpetrators (corruption) and cause a long-term deterrent effect and potential perpetrators (corruptors) who want to commit corruption crimes think long to commit corruption crimes (deterrent effect). If this legislative function is not used to form effective and radical corruption prevention and eradication laws, it will lead to public distrust of the House of Representatives. This can lead to an increase in the crime of corruption in the management of state finances.